2014
DOI: 10.1200/jco.2014.56.3809
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Neratinib in Combination With Capecitabine in Patients With Metastatic Human Epidermal Growth Factor Receptor 2–Positive Breast Cancer

Abstract: Neratinib in combination with capecitabine had a manageable toxicity profile and showed promising antitumor activity in patients with HER2-positive metastatic breast cancer pretreated with trastuzumab and lapatinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(73 citation statements)
references
References 28 publications
1
71
1
Order By: Relevance
“…Considerably higher overall response rates were observed when neratinib was combined with chemotherapeutic agents, notably paclitaxel (73%) [64] and capecitabine (63%) [70] (Table 3), findings that have prompted larger randomized trials of these combinations. The results from the first of these studies -NEfERT-T -have recently been reported [69] (Table 3).…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 94%
See 1 more Smart Citation
“…Considerably higher overall response rates were observed when neratinib was combined with chemotherapeutic agents, notably paclitaxel (73%) [64] and capecitabine (63%) [70] (Table 3), findings that have prompted larger randomized trials of these combinations. The results from the first of these studies -NEfERT-T -have recently been reported [69] (Table 3).…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 94%
“…Early phase II trials indicated that single-agent neratinib has efficacy in trastuzumab-pretreated patients [61,66], and subsequent trials showed that this effect could be enhanced through combination with either chemotherapeutic agents (i.e. capecitabine, vinorelbine) [63,70] or temsirolimus [73]. NALA -an active phase III trial -is comparing neratinib in combination with capecitabine with standard third-line therapy, lapatinib plus capecitabine, in patients who have progressed after two or more HER2-directed regimens for metastatic disease.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Patients with trastuzumab pretreated HER2-positive metastatic breast cancer receiving neratinib plus capecitabine had an overall response rate of 64 % for those with no prior lapatinib therapy and 57 % for those previously treated with labtinib [54]. A recent news release from Puma Biotechnology, currently developing neratinib, states a positive effect in a randomized phase III trial of using neratinib in extended adjuvant therapy after adjuvant therapy with trastuzumab (http://www.pumabiotechnology.…”
Section: Discussionmentioning
confidence: 95%
“…HKI-272 is an irreversible, small molecule, tyrosine kinase inhibitor of HER1, HER2, and HER4 that is orally bioavailable (129). This trial has approximately 105 participants across 3 arms.…”
Section: Effects Of Egfr- and Her2-targeted Therapies On Breast Camentioning
confidence: 99%